Meningkatkan kemampuan pemecahan masalah matematis siswa SMP IT Al-Ajwa Al-Islamy kelas VII melalui model discovery learning berbantuan video animasi - Agustin, Amellia Putri; Sabandar, Jozua; Novtiar, Chandra (IKIP Siliwangi, 2024)
This research aims to see the improvement in mathematical problem solving abilities of class VII middle school students through the Discovery Learning Learning Model assisted by animated videos. This research is experimental research. The population in this study were class VII students, while the sample was students from class VII A as the experimental class and VII B as the control class at SMP IT Al-ajwa Al-Islamy. This research uses the Nonequivalent Pretest-Posttest Control Group Design research design. The research instrument used was an essay question with a total of 7 questions. The data obtained will be analyzed and processed using a 2 independent sample test using a normality test, a homogeneity test first as a prerequisite and followed by a t-test. The results of hypothesis testing using the Independent Sample T-Test show that the significant value is 0.000 ≤ 0.05, so is rejected. So, it can be concluded that the Discovery Learning Model assisted by animated videos to improve the mathematical problem solving abilities of Al-Ajwa Al-Islamy IT Middle School students is better and has increased.